Esa1p Is an Essential Histone Acetyltransferase Required for Cell Cycle Progression - Clarke, Astrid S. (American Society for Microbiology, 1999)
Histones are dynamically modified during chromatin assembly, as specific transcriptional patterns are established, and during mitosis and development. Modifications include acetylation, phosphorylation, ubiquitination, methylation, and ADP-ribosylation, but the biological significance of each of these is not well understood. For example, distinct acetylation patterns correlate with nucleosome formation and with transcriptionally activated or silenced chromatin, yet mutations in genes encoding several yeast histone acetyltransferase (HAT) activities result in either no cellular phenotype or only modest growth defects. Here we report characterization of ESA1, an essential gene that is a member of the MYST family that includes two yeast silencing genes, human genes associated with leukemia and with the human immunodeficiency virus type 1 Tat protein, and Drosophila mof, a gene essential for male dosage compensation. Esa1p acetylates histones in a pattern distinct from those of other yeast enzymes, and temperature-sensitive mutant alleles abolish enzymatic activity in vitro and result in partial loss of an acetylated isoform of histone H4 in vivo. Strains carrying these mutations are also blocked in the cell cycle such that at restrictive temperatures, esa1 mutants succeed in replicating their DNA but fail to proceed normally through mitosis and cytokinesis. Recent studies show that Esa1p enhances transcription in vitro and thus may modulate expression of genes important for cell cycle control. These observations therefore link an essential HAT activity to cell cycle progression, potentially through discrete transcriptional regulatory events.